Analisis Kemampuan Pemahaman Konsep Matematis Ditinjau dari Kemandirian Belajar pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Devi, Kristina; Hartono, Hartono; Irvandi, Wandra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to describe students' ability to understand mathematical concepts from the independent learning of SPLDV material. The type of research used in this study is descriptive. The form of research used in this study is a qualitative form. The data collection technique used is interview guidelines. questionnaires, tests and research documents. The analysis steps in this study are data collection, data reduction, data presentation and conclusion drawing. The results of this study, it can be concluded that students with high understanding abilities can solve problems with several methods/ways. Students with moderate understanding abilities can only use one method/way in solving problems that are remembered or understood and students can state what is known and asked from the problem, can make variable examples and make mathematical models, then students understand the steps to solve the problem but students do not associate concepts internally and externally so that errors occur in the calculation process. Low-ability students are able to understand the problem and can state what is known and asked from the question, but students are confused about solving the problem and are confused about what method to use to solve the problem.